Curse of the Narrows - MacDonald, Laura 1963- (Walker & Co. Distributed to the trade by Holtzbrinck Publishers, 2005)
December 6, 1917. Halifax, Nova Scotia. A munitions ship collided with another vessel in the Narrows of the harbor, triggering a catastrophic explosion that destroyed much of the city. Within minutes a tsunami engulfed parts of the waterfront. That evening a blizzard buried Halifax, isolating it from the world.